IGF-1-induced Muscle-Derived Stem Cells as a Potential Treatment of Stress Urinary Incontinence in Female Rats - Chen, Chunjing; Xu, Ying; Song, Yanfeng (Urology Journal, 2022)
Purpose: Stress urinary incontinence (SUI) is prevalent among elderly women. This study aimed to discuss the potential of muscle-derived stem cells (MDSCs)-based therapy in treating SUI by exploring the effect of Insulin-like growth factor-1 (IGF-1) on transplanted MDSC and urethral sphincter function. Materials and Methods: Bilaterally pudendal nerve-transected (PNT) female rats were divided into four groups: sham, PNT+ phosphate buffered solution (PBS) injection, PNT+IGF-1/MDSCs and PNT+ green fluorescent protein (GFP)/MDSCs. IGF-1 was expressed in MDSCs by lentiviral vector. Viable MDSCs were detected by laser scanning confocal microscopy (LSCM). The expression of Myosin heavy chain (MyHC), vascular endothelial growth factor (VEGF), VEGF receptor 2 (VEGFR-2), microvessel density (MID) and urethral resistance function were assessed. Results: IGF-1 promoted the survival and differentiation of MDSCs. IGF-1-expressing MDSCs facilitated local angiogenesis and muscle fiber regeneration, and alleviated symptoms of SUI. Conclusions: IGF-1-expressing MDSCs may be used as a novel treatment for patients with SUI.